LncRNA Miat knockdown alleviates endothelial cell injury through regulation of miR‐214‐3p/Caspase‐1 signalling during atherogenesis. (5th August 2021) - Li, Tao; Tu, Peiyang; Bi, Jianbo; Sun, Yanling; Yu, Dejun; Wang, Jinghao; Zhao, Baoshan
Abstract: Atherosclerosis is a common problem in healthy people around the world. Long noncoding RNAs (lncRNAs) play important roles in atherosclerosis. Myocardial infarction‐associated transcript (Miat) is a cardiovascular disease‐associated lncRNA. Its role and mechanism in atherosclerosis is still not fully clarified. Our study aims to explore the role and mechanism of lncRNA Miat in atherosclerosis. The atherosclerosis models were established both in vitro and in vivo. Real‐time PCR was used to measure the expression of lncRNA Miat, miR‐214, Caspase‐1 and IL‐1β. Western blot was performed to detect the protein expression of Caspase‐1. CCK‐8 assay, Tunel staining, and flow cytometry analysis were conducted to detect proliferation and apoptosis of human aortic endothelial cells (HAECs), respectively. Oil red O staining and HE staining were used to evaluated the histological changes of the aorta. The results found that lncRNA Miat was upregulated in ox‐LDL‐induced atherosclerosis model in vitro. The inhibition of lncRNA Miat protects against ox‐LDL‐induced HAEC injury, presented as increased cell viability and decreased apoptosis. LncRNA Miat and miR‐214 has binding site, and CASP1, which encodes Caspase‐1, is a target of miR‐214. The downregulation of lncRNA Miat increased the expression of miR‐214‐3p and decreased the expression of Caspase‐1, as well as its downstream molecule IL‐1β in HAECs. However, the inhibition of miR‐214‐3p attenuated the effect of lncRNA Miat downregulation on HAECs. Furthermore, the downregulation of lncRNA Miat alleviated atherosclerosis in ApoE‐deficient mice. Correspondingly, the expression of miR‐214‐3p was upregulated and Caspase‐1 was downregulated after knockdown of lncRNA Miat. In conclusion, downregulation of lncRNA Miat exerts a protective effect against atherosclerosis through the regulation miR‐214‐3p/Caspase‐1 signalling pathway. Therefore, the inhibition of lncRNA Miat expression may be an effective strategy in the treatment of atherosclerosis.